Fatores clínicos e metabólicos em mulheres com diabetes mellitus gestacional e associação com adipocitocinas plasmáticas - Elaine Belem Figueiredo (2011)
BACKGROUND: Gestational diabetes mellitus (GDM) increases the risk of developing type 2 diabetes mellitus (T2DM). The main clinical and metabolic factors associated with the occurrence of T2DM in women with GDM, are severity of glucose intolerance during pregnancy and after delivery, overweight and obesity, family history of T2 DM and factors that have recently been suggested as possible predictors for diabetes - the adipocytokines. OBJECTIVES: To identify clinical and metabolic factors present in women diagnosed with GDM and correlate them to the plasma adipocytokines, adiponectin and leptin, and plasma metabolites (total cholesterol, triglycerides and glucose). RESULTS: The maternal age was 32.5 ± 4.2 years. The presence of family history of diabetes was 77.6% (52), gestational age at diagnosis of GDM was 25.4 ± 5.0 weeks, and blood glucose levels in OGTT 2h 162.9 ± 24.1 mg/dl. 30,0% (20) of the women was using insulin replacement therapy. 32.8% (22) were overweight and in the third quarter, 49.2% (32) obesity. The concentrations of adiponectin in the third trimester of pregnancy are correlated with variables of diagnosis of GDM, as the week of diagnosis (r=0.561, p=0.002) and OGTT results two hours after challenge with a solution of glucose (r=-0.556, p=0.001). There was no significant correlation between adiponectin and BMI before pregnancy or in the third quarter, as well as between adiponectin and glucose concentration in the third trimester (r=0.121, p=0.540, r=0.185, p=0.320 and r=-0.191, p=0.303, respectively). Leptin concentrations in the third quarter were positively correlated with blood glucose levels at diagnosis, and fasting OGTT (r=0.449, p=0.028). CONCLUSION: This study highlights the presence of family history of diabetes, insulin replacement during pregnancy, prepregnancy overweight and obesity in pregnancy as a potencial factors involved in the later development of T2 DM. The plasma adipocytokines levels is associated with metabolic and clinical factors involved in the occurrence of T2DM. The results suggest that adipocytokines leptin and adiponectin may be associated with severity of GDM, and therefore are important indicators of the risk of occurrence of DM2 in this population.